Resilience Analysis Framework for a Water–Energy–Food Nexus System Under Climate Change - Ioannou, Alexandra E.; Laspidou, Chrysi S. (Frontiers in Environmental Science, 2022)
Climate change impacts the Water-Energy-Food security; given the complexities of interlinkages in the nexus system, these effects may become exacerbated when feedback loops magnify detrimental effects and create vicious cycles. Resilience is understood as the system’s adaptive ability to maintain its functionality even when the system is being affected by a disturbance or shock; in WEF Nexus systems, climate change impacts are considered as disturbances/shocks and may affect the system in different ways, depending on its resilience. Future global challenges will severely affect all vital resources and threaten environmental resilience. In this article, we present a Resilience Analysis Framework for a Water-Energy-Food Nexus system under climate change, and we identify how such systems can become more resilient with the implementation of policies. We showcase results in the national case study of Greece. Parametric Sensitivity Analysis for socio-ecological systems is performed to identify which parameter the model is most sensitive to. The case study is based on the structure of a System Dynamics Model that maps sector-specific data from major national and international databases while Causal Loop Diagrams and Stock-and-Flow Diagrams are presented. Through engineering and ecological resilience metrics, we quantify system resilience and identify which policy renders the system more resilient in terms of how much perturbation it can absorb and how fast it bounces back to its original state, if at all. Two policies are tested, and the framework is implemented to identify which policy is most beneficial for the system in terms of resilience.